2016
DOI: 10.5530/pj.2017.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of isolated compounds from the stem bark of Garcinia cowa Roxb

Abstract: Objective: To find the anti inflammatory active compounds from methanol extract of Garcinia cowa Methods: To evaluate the inhibitory activity of isolated compounds on nitric oxide (NO) production, culture media was assayed using Griess reaction. An equal volume of Griess reagent (1% sulphanilamide and 0.1% N-(L-naphthyl)-ethylene diamine dihydrochloride, dissolved in 2.5% H3PO4) was mixed with culture supernatant and color development was measured at 550 nm using a micro plate reader. The amount of nitrite in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…Phytochemical studies and pharmacological activities of G. cowa from Thailand were reported recently [2 -6]. According to previous reports, main chemical constituents of G. cowa are xanthones which were demonstrated interesting bioactivities such as antimalarial [2], antimicrobial [3,5,7], anti-inflammatory [4,8], antioxidant [3,4,9], antibacterial [5,10,11], antitumor-promoting activity [12] and cytotoxic activities [13 -15].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies and pharmacological activities of G. cowa from Thailand were reported recently [2 -6]. According to previous reports, main chemical constituents of G. cowa are xanthones which were demonstrated interesting bioactivities such as antimalarial [2], antimicrobial [3,5,7], anti-inflammatory [4,8], antioxidant [3,4,9], antibacterial [5,10,11], antitumor-promoting activity [12] and cytotoxic activities [13 -15].…”
Section: Introductionmentioning
confidence: 99%
“…9 It also has anticancer activity against MCF-7, DU-145 and H-460 6 as well as can reduce levels of total cholesterol and triglyceride levels in the blood of male rats. 10 This compound was also reported had anti inflammatory 11 and anti platelet activity. 12 The latex of this plant has been used for traditional medicine for centuries and also was one of the source of rubraxanthone.…”
Section: Introductionmentioning
confidence: 92%
“…NSAIDs and opioids which are effective for the treatment of inflammation and pain. [7][8] These drugs block COX-1 and COX-2 enzymes involved in prostaglandin production. However, their chronic use particularly in patients with arthritis or other chronic inflammatory diseases is associated with adverse effects such as gastrointestinal perforation, ulceration, bleeding and renal toxicity mainly due to the blockade of COX-1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the need arises for the development of newer anti-inflammatory and analgesic agents from natural sources with more powerful activity and with lesser side effects as substitutes for chemical therapeutics. [7][8][9][10] In this context the present study was executed to explore for more naturally available alternatives, so that their therapeutic values can be assessed and expanded. Several epidemiological studies have suggested that the consumption of fruit and vegetables is associated with a reduced risk of cardiovascular disorders and cancers, [10][11] and neurodegenerative diseases such as Parkinson's and Alzheimer's diseases, 12 as well as S173 positive effects on inflammation and aging.…”
Section: Introductionmentioning
confidence: 99%